Temperature field characterization and optimization of temperature field distribution in pipe lining process based on electromagnetic induction heating system - Yuzhong Wang (Elsevier, 2021)
It is a promising treatment strategy to use an induction heating system for pipe lining, which can void the low efficiency and difficult temperature control of the traditional flame and hot air heating. In this study, a novel finite element model of pipe scanning induction heating was established, and the reliability of the model was verified through experiments. In addition, through the Plackett-Burman design, the main factors affecting the temperature fluctuation at 5 mm of the lining layer are analyzed. Finally, based on the analysis results, the system parameters were optimized by response surface method and the parameter configuration of the induction heating system with the minimum temperature fluctuation of 5 mm lining layer was obtained. The model established in this paper greatly reduces the calculation time of the electromagnetic induction heating finite element model of the moving magnetic field. It can be applied to the temperature information prediction of the lining induction heating where high-temperature accuracy is required and provides a reference for the characterization of the lining induction heating system and its application in low-temperature heat treatment, and the modeling strategy can be extended to the characterization of the temperature field evolution of any mobile heat source.